Separation of Syringin and Flavonoids from Saussurea involucrata by Macroporous Resin - Yao, L.Y.; Wang, L.W.; Zhao, B.; Yuan, X.F.; Wang, X.D.; Wang, Y.C.; Su, H.M.; Niu, S.M. (Asian Journal of Chemistry, 2011)
The performance and separation characteristics of nine macroporous resins for the enrichment and purification of flavonoids and syringin from planted Saussurea involucrata extracts were evaluated. The experimental results showed that a resin labeled X-5 offered higher adsorption and desorption capacities and higher adsorption speed for syringin and flavonoids than other resins and its adsorption data fit to the Freundlich isotherm. The dynamic adsorption and desorption experiments were carried out in the column packed with X-5 resin to optimize the separation process. An enriched flavonoids extract without syringin and an enriched syringin extract with 80.3 % purity could be separated from crude Saussurea involucrata extracts in one run. The results showed that X-5 resin had a good ability to separate syringin and flavonoids from planted Saussurea involucrata. This method would be very useful and has important significance for the protection of wild Saussurea involucrata.